Gallant_Anna_MAET_2007.pdf - Covenant Theological Seminary (St. Louis, Missouri : Covenant Theological Seminary, 2024)
1 online resource (PDF); Abstract; Typescript (photocopy); Thesis (M.A.E.T.)--Covenant Theological Seminary; Bibliography: